PARTISIPASI ORANG TUA DALAM PERENCANAAN PENDIDIKAN DI SMKN 1 SUNGAI TABUK - Arief Prasetya, Muhammad; Rahmaniah; Sulistiyana; Suhaimi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Parental participation plays an important role in supporting the implementation of education in schools. Parents’ involvement does not only support students’ learning processes but also contributes to the development of school educational programs. This study aims to examine parental participation in educational planning at SMKN 1 Sungai Tabuk and to identify the strategic role of parents in supporting students’ career development. This research employed a qualitative descriptive approach. Data were collected through interviews with the principal, the vice principal for curriculum, and the vice principal for public relations. The results indicate that parental participation occurs in several school activities such as new student admissions, report card distribution, preparation for industrial work practice (PKL), and graduation activities. Communication between schools and parents is conducted through the school committee, direct meetings, and digital communication media such as WhatsApp groups. In the context of vocational education, parents also play a strategic role in supporting students’ career development through their social networks which can help provide internship placements and job opportunity information for graduates. However, parental involvement is sometimes constrained by parents’ work commitments. Therefore, strengthening communication and cooperation between schools and parents is necessary to enhance parental participation in educational planning.